Description of a new species of arboreal rat of the Rhipidomys fulviventergroup, from Venezuela (Rodentia: Cricetidae). / Descripción de una nueva especie de rata arborícola del grupoRhipidomys fulviventer, de Venezuela (Rodentia: Cricetidae) - García, Franger J.; Almeida, Talita G.; Machado, Marjorie; Delgado-Jaramillo, Mariana Isabel; Araujo-Reyes, Dayana; Vásquez-Parra, Oriana; Flórez, Guillermo (Anartia, 2020)
ABSTRACT Arboreal rats of the genus Rhipidomys, belong to a taxonomic group of Neotropical distribution, included in the tribe Thomasomyini. In Venezuela, the Rhipidomys fulviventer group contains four taxa (R. fulviventer, R. tenuicauda, R. venus-tus, and R. wetzeli), only found in high elevation cloud forests and lowland rainforests. Because collections to date do not represent a thorough sampling of their geographic range, taxonomic arrangement of some taxa (e. g., Rhipidomys venustus), has been controversial. However, new specimens collected in recent years provide novel insights into the biogeographic variation of the genus Rhipidomys. In this article, we evaluate the taxonomy and geographic distribution of R. venustusbased on a morphometric and morphological review that included integument, skull, teeth and post-cranial skeleton. Specimens examined cover the entire geographic range of this species. The results showed significant differences between populations, and supports the recognition of a new species inhabiting cloud forests in the Cordillera de la Costa Central and the Sistemas de colinas Lara-Falcón, Venezuela. The new species is larger than any of its congeners in the R. fulviventergroup in this country. It shows dorsal and ventral coloration differences and unique qualitative characters associated with integument, skull and post-cranial skeleton. The geographic distribution of R. venustus is updated, and restricted to the Cordillera de Mérida. Remarks on the ecolog y and conservation status of the new taxon are also presented. RESUMEN Las ratas arborícolas del género Rhipidomys, pertenecen a un grupo taxonómico de distribución Neotropical, incluidas en la Tribu Thomasomyini. En Venezuela, el grupo Rhipidomys fulviventer está conformado por cuatro especies (R. fulviven-ter,R. tenuicauda, R. venustus y R. wetzeli), las cuales se encuentran en áreas boscosas, tanto en selvas nubladas de altura como en bosques lluviosos de tierras bajas. Debido a que hasta la fecha las colecciones de estos roedores no representan la totalidad de sus distribuciones geográficas, la ubicación taxonómica de algunas especies (e. g., Rhipidomys venustus), ha sido controversial. Sin embargo, muestras biológicas obtenidas en años recientes ofrecen una nueva percepción de la variación biogeográfica del género Rhipidomys. En este trabajo evaluamos la taxonomía y la distribución geográfica de R. venustusbasados en una revisión morfométrica y morfológica que incluye integumento, cráneo, dientes y esqueleto post-craneal. Los ejemplares examinados cubren la totalidad de la distribución geográfica de esta especie. Los resultados mostraron dife-rencias significativas entre las distintas poblaciones y apoyan el reconocimiento de una nueva especie que habita los bosques nublados de la Cordillera de la Costa Central y del Sistema de colinas Lara-Falcón, en Venezuela. Esta nueva especie es la de mayor talla dentro de las otras que conforman el grupo Rhipidomys fulviventer en este país. Posee diferencias de colo-ración dorsal y ventral y caracteres cualitativos únicos asociados con el integumento, el cráneo y el esqueleto post-craneal. Finalmente, actualizamos la distribución geográfica de R. venustus, la cual se restringe a la Cordillera de Mérida. Se enfatiza además sobre la ecología y el estado de conservación del nuevo taxón.